Biochar—just a black matter is not enough - Hornung, Andreas; Stenzel, Fabian; Grunwald, Jan (Biomass Conversion and Biorefinery, 2021)
What differs biochar from charcoal? The simple answer is that biochar is a carbon-rich product obtained from the thermal decomposition of organic material, at the presence of no or only a bit of oxygen. In principle, the production of biochar is comparable to the production of charcoal, one of the oldest and most established processes developed by mankind. While charcoal is made traditionally from wood, biochar can be based on a wide range of biomass and biomass residues. However, a variety of technologies for the production of biochar has been developed in recent years. The technologies are based on pyrolysis, gasification, or hydrothermal carbonization and are ranging from simple units, like heated steel drums to full automated and controlled processes. Therefore, the obtained products have tremendous differences in its properties and resulting qualities. The quality defines the field of application. To obtain the required quality for each application, the right process must be applied. Consequently, it is not enough only to enrich the carbon content by thermal decomposition of organic material. The production of tailor-made biochar for specific high added–value application is much more complex. In addition, side products like liquid biofuels make business cases stronger. If it is done in the right way, biochar production combined with advanced biofuels can be an economic solution to overcome the problems of climate change. “So for the future of mankind, this black matter might give the light at the end of the tunnel.”
CRIS-Team Scopus Importer:2021-02-05
Keywords: Biochar; Carbon sequestration; Certification; EN-biofuels; Legal regulation; Thermochemical conversion